WEB BASED TAHFIDZ QUR’AN MANAGEMENT APPLICATION AT MAZROATUL LUGHOH ISLAMIC BOARDING SCHOOL - Mar’atus Sholihah; Maulidina Rahmawati Surya (Universitas Trunojoyo Madura, 2021)
This Web-Based Tahfidz Qur'an Management Application is an application or software designed to process data related to the target memorization and recap of students, especially at the Mazro'atul Lughoh Islamic Boarding School, Pare Kediri. The problem faced in this Islamic boarding school is in carrying out targeting guidelines and memorizing students who still use the manual method, namely via WatsApp. Because there are no more sophisticated applications to make it easier to store data and to access information. The purpose of making this Web-Based Tahfidz Qur'an Management Application is to make it easier for admins, teachers, students and guardians of students to input data, recap data, update data and access information that has been updated by the admin. The method used in the research.This application is a method of observation, literature study, interviews, system design and system testing. This program was developed using the PHP (Hypertext Preprocessor) programming language and MySQL database. The design is built using HTML and CSS. Using CodeIgniter Framework and SB admin 2 templates.